(untitled) (Texas Journal of Medical Science, 2023)
The article discusses the problem of compliance in terms of treatment of patients with chronic diseases. Lack of adherence to therapy (non-compliance) significantly reduces the effectiveness of treatment, and often negates all the efforts of doctors.